Borderlands and liminal subjects: transgressing the limits in philosophy and literature - Decker, Jessica Elbert ; Winchock, Dylan (Palgrave Macmillan, 2020)
Introduction: Borderlands and Liminality Across Philosophy and Literature / Jessica Elbert Decker and Dylan Winchock -- Ethics at the Border: Transmitting Migrant Experiences / Filippo Menozzi -- Land, Territory and Border: Liminality in Contemporary Israeli Literature / Adia Mendelson-Maoz -- Zones of Maximal Translatability: Borderspace and Women's Time / Heather H. Yeung -- A Search for Colonial Histories: The Conquest by Yxta Maya Murray / Salvador C. Fernández -- Transforming Borders: Resistant Liminality in Beloved, Song of Solomon, and Paradise / Danielle Russell -- "Gone Over on the Other Side:" Passing in Chesnutt's The House Behind the Cedars / Irina Negrea -- Queering and Gendering Aztlán: Anzaldúa's Feminist Reshaping of the Chicana/o Nation in the U.S.-Mexico Borderlands / Tereza Jiroutová Kynčlová -- Achilles and the (Sexual) History of Being / William Koch -- Borderland Spaces of the Third Kind: Erotic Agency in Plato and Octavia Butler / Jessica Elbert Decker -- Alice's Parallel Series: Carroll, Deleuze, and the 'Stuttering Sense' of the World / Andrea Oppo -- Cultural Liminality: Gender, Identity, and Margin in the Uncanny Stories of Elizabeth Bowen / Paromita Mukherjee -- Crossing the Utopian/Apocalyptic Border: The Anxiety of Forgetting in Paul Auster's In the Country of Last Things / Dylan Winchock